2009
DOI: 10.1002/adma.200803633
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Stabilization and Self‐Assembly of Graphene Sheets into Layered Bio‐Nanocomposites using DNA

Abstract: Atomically thick graphene layers produced from graphite reveal unique electro-thermal, and mechanical properties, [1][2][3][4][5][6][7] and are considered to have a wide range of applications in nanoelectronics, catalysis and biosensing. [1,3,[8][9][10] Graphene monolayers exhibiting exceptional electron/hole carrier mobility have been prepared by mechanical exfoliation of highly ordered pyrolytic graphite, [1,3] by epitaxial growth using chemical vapour deposition of hydrocarbons onto silicon carbide, [11] or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
304
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(319 citation statements)
references
References 36 publications
7
304
2
3
Order By: Relevance
“…For example, adsorption of DNA biomolecules on the surface of graphene is enabled due to non-covalent interactions (electrostatic/hydrogen bonding) between the primary amines of the single-stranded DNA and the carboxylic groups of the GO and by the π-π stacking interactions involving both purine and pyrimide bases of DNA. The results demonstrate that these systems are stable in aqueous solutions for several months at concentrations below 2.5 mg/mL (Patil, Vickery et al 2009). This approach was also developed for chains of double-stranded DNA, yet the results showed that the aqueous suspensions of graphene were less stable, probably due to the pairing of helices limiting interactions with the hydrophilic surface of GO.…”
Section: Wwwintechopencommentioning
confidence: 71%
“…For example, adsorption of DNA biomolecules on the surface of graphene is enabled due to non-covalent interactions (electrostatic/hydrogen bonding) between the primary amines of the single-stranded DNA and the carboxylic groups of the GO and by the π-π stacking interactions involving both purine and pyrimide bases of DNA. The results demonstrate that these systems are stable in aqueous solutions for several months at concentrations below 2.5 mg/mL (Patil, Vickery et al 2009). This approach was also developed for chains of double-stranded DNA, yet the results showed that the aqueous suspensions of graphene were less stable, probably due to the pairing of helices limiting interactions with the hydrophilic surface of GO.…”
Section: Wwwintechopencommentioning
confidence: 71%
“…Isothermal titration calorimetry experiments between graphene and nucleobases revealed that guanine presented the highest interaction energy followed by adenine, cytosine and thymine 17 . Moreover, GO has proven able to load both single-stranded DNA and RNA despite its overall negative charge thanks to hydrophobic and π-π stacking interactions between the ring structures present in NA nucleobases and the GO hexagonal carbon lattice 18,19 . On the other side, the adsorption of double-stranded NA onto GO flakes is thought to be more complex due to its hydrophilic external structure and less availability of NA bases trapped within the double helix structure 20 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…К числу химических реактивов, успешно применявшихся для восста-новления ОГ, в первую очередь относятся гидразин и его производные (см., например, работы [30,40,49,[56][57]). При этом гидразин не восстанавливает гидроксильные группы на краях нанолистов.…”
Section: результаты аппроксимации линии с1sunclassified